A Triptych of Care: An Anthropological Interpretation of Morning Bed‐Baths in Greek Intensive Care - Stelios Parissopoulos; Fiona Timmins; Marianna Mantzorou; George Tsakonitis; Meropi Mpouzika; Eleni Papagaroufali (Nursing Philosophy, 2026)
ABSTRACT This paper presents a focused analysis arising from a broader ethnographic study of nursing praxis, power relations, and clinical decision‐making in a Greek ICU. The aim of this paper is to explore the morning bed‐bath as a culturally embedded ICU nursing practice and to interpret how bodily care, professional identity, organisational routines and relational attentiveness intersect within this everyday activity. Informed by critical medical anthropology and phenomenology, the study draws on participant observation, ethnographic fieldnotes, and interviews with intensive care staff. The interpretation draws primarily on Foucault's concept of discipline, complemented by Bourdieu's notion of habitus and embodied practice, and Douglas's work on purity and symbolic order. Three interrelated themes emerged, forming a ‘triptych of care’: a) proximity and synchronicity to the patients' needs and clinical condition, which revealed skilled bodily attentiveness, clinical judgement and nursing agency, alongside negotiations of professional knowledge, and authority; b) the creation of a zone of safety and privacy, where bodily exposure, dignity, relational care, and professional interaction were negotiated within the ICU environment; and c) the removal of dirt and impurities, which served immediate clinical and hygienic purposes while also carrying cultural and professional meanings associated with bodily presentation, cleanliness, and order. The findings suggest that the morning bed‐bath in the ICU studied was not merely a technical nursing task, but a culturally embedded and routinised practice through which temporal and organisational routines, embodied care, symbolic order, and professional nursing values are enacted.